Aggravated food insecurity in COVID-19 era: quality seed flow of adapted and nutrient-dense varieties is central to the recovery equation in the drylands - Akpo, Essegbemon; Chris O. Ojiewo; Mequanint B. Melesse; Ganga Rao; James Mwololo; Eric Manyasa; Henry Ojulong; Rebbie Harawa; Rajeev K. Varshney (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The COVID-19 pandemic has disrupted every area of our daily activities and businesses. After the health crisis, the food crisis is the next battle to encounter, which will need to mobilize all energies to maintain social security and protect the citizens of the world. For sustained support and recovery of rural and urban populations, especially in the dryland areas of Sub-Saharan Africa, seed of the well-adapted, nutrient dense varieties should flow. The solution of quality seed flow equation is complex and involves several intervention areas, e.g., adapted and modern groundnut, chickpea, pigeonpea, sorghum and finger millet varieties, sustainable and long term approaches leveraging various seed production and delivery models, remote information and knowledge dissemination systems, digital seed production and delivery roadmaps, digitized variety release and promotion processes, smart food campaigns and trainings to promote good utilization of nutrient dense crops.